Learning OpenStack - Shrivastwa, Alok; Shrivastwa, Alok; Sarat, Sunil (Packt Publishing, 2015)
Set up and maintain your own cloud-based Infrastructure as a Service (IaaS) using OpenStackAbout This BookBuild and manage a cloud environment using just four virtual machinesGet to grips with mandatory as well as optional OpenStack components and know how they work togetherLeverage your cloud environment to provide Infrastructure as a Service (IaaS) with this practical, step-by-step guideWho This Book Is ForThis book is targeted at all aspiring administrators, architects, or students who want to build cloud environments using Openstack. Knowledge of IaaS or cloud computing is recommended.What You Will LearnGet an introduction to OpenStack and its componentsAuthenticate and authorize the cloud environment using KeystoneStore and retrieve data and images using storage components such as Cinder, Swift, and GlanceUse Nova to build a Cloud Computing fabric controllerAbstract technology-agnostic networks using the Neutron network componentGain an understanding of optional components such as Ceilometer, Trove, Ironic, Sahara, Barbican, Zaqar, Designate, Manila, and many moreSee how all of the OpenStack components collaborate to provide IaaS to usersCreate a production-grade OpenStack and automate your OpenStack CloudIn DetailOpenStack is a free and open source cloud computing platform that is rapidly gaining popularity in Enterprise data centres. It is a scalable operating system and is used to build private and public clouds. It is imperative for all the aspiring cloud administrators to possess OpenStack skills if they want to succeed in the cloud-led IT infrastructure space.This book will help you gain a clearer understanding of OpenStack's components and their interaction with each other to build a cloud environment. You will learn to deploy a self-service based cloud using just four virtual machines and standard networking.You begin with an introduction on the basics of cloud computing. This is followed by a brief look into the need for authentication and authorization, the different aspects of dashboards, cloud computing fabric controllers, along with (3z(BNetworking as a Service(3y (Band (3z(BSoftware Defined Networking.(3y (BThen, you will focus on installing, configuring, and troubleshooting different architectures such as Keystone, Horizon, Nova, Neutron, Cinder, Swift, and Glance. Furthermore, you will see how all of the OpenStack components come together in providing IaaS to users. Finally, you will take your OpenStack cloud to the next level by integrating it with other IT ecosystem elements before automation.By the end of this book, you will be proficient with the fundamentals and application of OpenStack.Style and approachThis is a practical step-by-step guide comprising of installation prerequisites and basic troubleshooting instructions to help you build an error-free OpenStack cloud easily.s